Incidence and Surgical Importance of Zuckerkandl's Tubercle of the Thyroid and Its Relations with Recurrent Laryngeal Nerve. (16th August 2012) - Gurleyik, Emin; Gurleyik, Gunay
Abstract : Background . Variations of recurrent laryngeal nerve (RLN) and Zuckerkandl's tubercle (ZT), which is posterior extension of lateral lobes, may affect safety of thyroidectomy. Methods . Total and hemithyroidectomy were surgical procedures in 60 and 40 patients, respectively. Surgical anatomy was studied in 87 right and 73 left lobes. Presence of ZT was noted and its incidence was determined. RLNs were identified and fully isolated. Relationship between ZT and RLN was established. Results . ZTs were identified in 66 (66%) patients and in 81 (51%) lobes. ZT was present in 53 (61%) right and in 28 (38%) left lobes. ZTs were bilateral in 15 (25%) of 60 total thyroidectomy cases. Smaller tubercles show the neurovascular crossing point. RLN was posterior (medial) to ZT in 76 (94%) occurrences. RLN was laying on anterior surface of ZT only in 5 (6%) instances. Conclusions . RLN is unusually laying lateral to ZT which is common structure in the thyroid. Lateral RLN may be more vulnerable to injury. Total thyroidectomy requires dissection of ZT adjacent to RLN. Based on unusual relations and variations, RLN should be fully isolated before excision of adjacent structures.